Fermentasi Kelapa Parut Bebas Protein dengan Aspergillus niger untuk Menghasilkan Lipase: Fermentation of Protein-Free Grated Coconut with Aspergillus niger to Produce of Lipase - Rifka Aulia; Syaiful Bahri; Meryany Ananda (KOVALEN: Jurnal Riset Kimia, 2020)
The research about the fermentation of protein-free grated coconut with Aspergillus niger to produce of crude lipase enzyme has been carried out. This study aims to determine the effect of water content on fermentation medium and the incubation time which results lipase enzyme extract with the highest activity. This study used a Completely Randomized Design (CRD) consisting of 2 factors, i.e. variations of water content in medium of 40%, 50%, 60%, and 70% and incubation times of 48, 96, 144, and 192 hours. The parameters observed were lipase enzyme activity produced in each treatment. The results showed that the highest medium water content was 70% with the lipase enzyme activity 4.33 µmol/mL.minute and the best incubation time was 96 hours with the lipase enzyme activity of 0.83 µmol/mL.minute. Keywords: Lipase enzyme, protein-free grated coconut, Aspergillus niger